2017
DOI: 10.1155/2017/9152632
|View full text |Cite
|
Sign up to set email alerts
|

Vibration of a Cylindrical Tunnel under a Centric Point-Source Explosion

Abstract: Underground tunnels are vulnerable to terrorists' bombing attacks, which calls for studies on tunnel's response to internal explosive loading. In this paper, the dynamic response of a cylindrical tunnel to an ideal centric point explosion was treated as an axisymmetric 2-dimensional problem, in which the tunnel was modeled with a continuous anisotropic shell, while the ground medium's effect was accounted for with linear elastic Winkler springs and the explosive loading described by a temporal and spatial func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…By comparing the monitoring data in Table 1, it can be seen that the blasting vibration produced by the blasting excavation of Section IV is the largest, which indicates that the smaller the distance between the upper and lower tunnels, the larger the blasting vibration. at is to say, the blasting vibration of the upper and lower crossing tunnels also conforms to the general blasting vibration law that the vibration speed is inversely proportional to the distance between the blast centers [20,21]. e peak velocity of the measurement Point A (that is, the location of the tunnel lining dome) is the largest during the blasting process of each section, which indicates that the blasting excavation has the greatest influence on the vault of the existing tunnel.…”
Section: Vibration Monitoringmentioning
confidence: 90%
“…By comparing the monitoring data in Table 1, it can be seen that the blasting vibration produced by the blasting excavation of Section IV is the largest, which indicates that the smaller the distance between the upper and lower tunnels, the larger the blasting vibration. at is to say, the blasting vibration of the upper and lower crossing tunnels also conforms to the general blasting vibration law that the vibration speed is inversely proportional to the distance between the blast centers [20,21]. e peak velocity of the measurement Point A (that is, the location of the tunnel lining dome) is the largest during the blasting process of each section, which indicates that the blasting excavation has the greatest influence on the vault of the existing tunnel.…”
Section: Vibration Monitoringmentioning
confidence: 90%
“…It was observed that, with an increase in the distance from the source of explosion, the acceleration on the tunnel keeps on decreasing. Zhao et al [57] studied the response of a cylindrical tunnel against a centric point explosion. An expansion and a contraction phase were observed from the vibrations of the cylindrical shell.…”
Section: Influence Of Shape Of Tunnelsmentioning
confidence: 99%
“…More importantly, for shield tunnels in saturated soils, if a large deformation of the structure occurs and a hole is formed, a large amount of silt will then pour into the interior of the tunnel, causing secondary damage and triggering an even greater disaster. It has been reported that in the underground structure in New York City across the Hudson River section due to the long time of construction, a small explosion may cause perforation; if the river water enters into the tunnel, the consequences will be catastrophic [1,2], and many cities, such as London, Paris, Tokyo, and Singapore, in the world underground lines contain sections across the river and many cities in the south of China. The top of the underground tunnels is buried in shallow depths [3,4], which are more dangerous when subjected to external impact loads, such as the Shanghai Chongming Crossing river tunnel at an average depth of 9 m, and the shallowest depth is only 6.8 m [5].…”
Section: Introductionmentioning
confidence: 99%